Psychosocial stress has weaker than expected effects on episodic memory and related cognitive abilities: A meta-analysis. (January 2022) - McManus, Elizabeth; Talmi, Deborah; Haroon, Hamied; Muhlert, Nils
Highlights: Overall small positive effect of post-learning psychosocial stress on episodic memory. No other significant effects of psychosocial stress on episodic memory encoding or retrieval. Significant effects of stimuli valence during psychosocial stress, indicating possible interaction between stimuli type and the timing of stress. Overall, small significant negative effect of psychosocial stress on executive function - may help explain why certain memory processes are influenced by stress. Abstract: The impact of stress on episodic memory and related cognitive abilities is well documented in both animal and human literature. However, it is unclear whether the same cognitive effects result from all forms of stress – in particular psychosocial stress. This review systematically explored the effects of psychosocial stress on episodic memory and associated cognitive abilities. PubMed, PsycInfo, and Web of Science databases were searched. Fifty-one studies were identified and compared based on the timing of stress induction. A small positive effect of post-learning psychosocial stress with a long retention interval was shown. No other effects of psychosocial stress were seen. Re-analysis of previous meta-analyses also showed no significant effect of psychosocial stress on episodic memory, highlighting potentially different effects between stressor types. Psychosocial stress also had a moderately different effect when emotional vs. neutral stimuli were compared. Finally, psychosocial stress also decreased performance on executive function, but not working memory tasks. Our findings demonstrate that psychosocial stress may not have the clear effects on episodic memory previously ascribed to it.